Seed grafting of hevea. I: Potential viability - Preliminary Results - Pereira, Jomar da Paes; Moraes, Vicente H. de F.; Carvalho, Cláudio José R. de; Silva, Hércules Martins e (Pesquisa Agropecuaria Brasileira, 2014)
Cleft grafting of rubber trees have been tried with some promising results when apical parts 3-4 cm long were used as scions grafted on to seeds with two-five days after emergence of epicotyl. Better results were obtained when the two lateral cotyledonary buds were left to sprout and grow untill a good callus union was formed between scion and rootstock. In this case, callus was evident after seven days of the graft operation. Scion started flushing withing 21 days. As a result of the exhaustion of seed reserves, due to growth of lateral shoots, these first flushes showed a stunted growth. The second flushes were longer and more vigorous than the first ones, and this is interpreted as the result of the improvement of the graft union and better root growth.